Chapter 1 Swiss and (Anglo)-Dutch multinationals and organizational change in the era of Total War - Kurosawa, Takafumi (Taylor & Francis, 2019)
This chapter aims to explore organisational change as a result of political and security risks faced by four major European multinationals, Roche (pharmaceuticals), Nestlé (food), Unilever (non-mineral oil, fats, food and soap), and Philips (incandescent lamps, electronics), originally domiciled partly or wholly in what were two relatively small neutral countries-Switzerland and the Netherlands. Questions considered include how both world wars and nationalistic economic policy affected the organisational structures of these four companies, and the extent to which these changes had long-term consequences for their organisational and legal structures. The chapter focusses on several key themes, including localisation (adaption to national circumstances), decentralisation, taxation, the formation of holding companies, twin corporate structures, and geographical relocation. In all four cases, the companies survived mounting nationalism and the division of markets during and between the two world wars by localising their corporate organisation, and by doubling and dispersing headquarter functions. As a result, these European multinationals all eventually came to have a relatively decentralised form of organisation. Although the four companies manifested similar organisational responses, on closer examination the political circumstances between Dutch, Swiss and Anglo-Dutch companies differed to a large extent, and therefore a one-size-fits-all analytical approach does not apply.